Factors influencing the retrofitting of existing office buildings using Adelaide, South Australia as a case study. Issue 2 (11th May 2015) - Bruce, Toby; Zuo, Jian; Rameezdeen, Raufdeen; Pullen, Stephen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the barriers preventing investment in the re-use of low-grade multi-storey building stock in order to identify attributes that determine whether an existing building is suitable for retrofitting. Design/methodology/approach – Semi-structured interviews were undertaken with key industry practitioners to investigate existing practices and barriers facing low-grade building retrofits and what "ideal" multi-storey building features represent a successful investment opportunity. Findings – The findings showed that tenant commitment is necessary before any project goes ahead and that there exist many barriers influencing the investment decision. These include: high levels of asbestos found in existing buildings; changes in the National Construction Code necessitating enhanced fire safety and disability access; heritage listing; lack of awareness; overestimation of costs involved on simple and effective energy efficiency upgrades and change in tenant demands towards modern and efficient open plan offices. Many low-grade structures are privately owned inherited assets where the owners lack the expertise and capital to undertake retrofitting effectively. Research limitations/implications – The study is focused on the Adelaide CBD in South Australia but the findings are relevant to other Australian cities. Practical implications – There is room in the market for more positive and influential schemes such as the Green Building Fund that encourage more energy efficiency upgrading of these buildings. Social implications – The greater occurrence of retrofitting and re-use of older buildings, rather than demolition and rebuilding, has advantages with regard to reducing the impact of buildings on the environment and promoting sustainability. Originality/value – The research has indicated certain features of older buildings which render them as suitable candidates for retrofitting and refurbishment.